THE ANALYSIS OF THE EFFECTIVENESS OF THROMBOPROPHYLAXIS AMONG PREGNANT WOMEN WITH MESENCHYMAL DYSPLASIA - E. G. Kudinova; A. P. Momot; N. V. Trukhacheva (Фармакоэкономика)
the analysis of the effectiveness of thromboprophylaxis among pregnant women with mesenchymal dysplasia was carried out. It was concluded that it reduces the risk of thrombohemorrhagic complications and accordingly the economic costs of medical care.